Uji efektivitas poc lidah buaya dan air cucian beras terhadap peningkatan produksi pakcoy (Brassica rapa L.) - Ningsih, Dwi Haryati; Nashruddin, Muhammad; Anwar, Muhammad (Jurnal Agrotek Ummat, 2024)
Efforts to increase food security require innovation in reducing the level of use of chemical fertilizers by utilizing organic fertilizers. The aims of the research are: 1) is the application of liquid organic fertilizer from aloe vera able to increase the production of pakcoy plants, 2) is the application of liquid organic fertilizer from rice washing water effective in increasing the production of pakcoy plants, and 3) is there an interaction between the application of liquid organic fertilizer made from aloe vera? crocodiles with liquid organic fertilizer made from rice washing water on the growth rate of pak choy plants. The method used is an experimental method with a Completely Randomized Design (CRD) with two (2) factorial levels. The first factor uses liquid organic fertilizer from rice washing water with 2 doses, namely B0 (without treatment); B1 (with 12.5 ml dose of liquid organic fertilizer from rice washing water). The second factor uses aloe vera liquid organic fertilizer with doses: L0 (without treatment); L1 (5ml dose); L2 (10ml dose); L3 (15ml dose) and L4 (20ml dose). Each factorial is repeated 3 times. The results of the research found that the use of liquid organic fertilizer from aloe vera was able to increase pak choy production effectively with maximum treatment at a dose of 20 ml, apart from that the use of liquid organic fertilizer from rice washing water at a dose of 12.5 ml also has a real influence on increasing pakchoy production. However, in the interaction between the two liquid organic fertilizers, no significant interaction was found between the two types of organic liquid fertilizer during the research process.